Effects of Chemical Stimulations on Shikonin and Derivatives in In Vitro Turkish Echium italicum L. Hairy Root Culture - Suzerer, Veysel; Tepe, Melike; Atilla, Devrim; Tilkat, Engin; Ozcan, Tamer; Ciftci, Yelda Ozden (Springer, 2019)
[No abstract available]